The Role of Japanese Children’s Literature as a Resource in Japanese Language Education - Shinohara, Misaki (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study examines the role of children’s literature in Japanese language education, emphasizing its educational value and theoretical foundations. Children’s literature not only aids students in enhancing their vocabulary and grammar but also provides insights into the culture, traditions, morals, and social perspectives that shape Japanese society. The study explores how children’s literature can be utilized in Japanese language education, focusing on its educational benefits and theoretical background. The language used in children’s literature is concise yet expressive, allowing learners to naturally encounter new words, common expressions, and stylistic patterns within the context of the story. Furthermore, these stories stimulate imaginations and emotions, making the learning process more engaging. From an educational standpoint, children’s literature illustrates the strong connection between language, culture, and identity. It supports a student-centred approach, encouraging students to reflect, interpret, and take ownership of their learning. In contrast to traditional teaching materials that often emphasize grammar, children’s literature provides a more comprehensive learning experience by integrating language and culture within narratives. This allows learners to envision scenes and characters, helping them understand words and expressions in real-life contexts. This study aims to discuss the rationale for incorporating Japanese children’s literature into Japanese language education. Children’s literature enriches the learning experience by serving as a meaningful bridge between language and culture. It also promotes communication skills, cultural awareness, and autonomous learning.